Exploratory Shopping: Attention Affects In-Store Exploration and Unplanned Purchasing - Streicher, Mathias C; Estes, Zachary; Büttner, Oliver B (Journal of Consumer Research, 2021)
A fundamental function of retailing is to bring products into the view of shoppers, because viewing products can activate forgotten or new needs. Retailers thus employ various strategies to entice shoppers to explore the product assortment and store environment, in the hopes of stimulating unplanned purchasing. This article investigates consumers’ breadth of attention as a mechanism of such in-store exploration and hence of unplanned purchasing. Specifically, attentional breadth is the focus that is directed to a wider or more limited area in processing visual scenes. Across several lab and field experiments, the authors show that shoppers’ attentional breadth activates an exploratory mindset that stimulates visual and physical exploration of shopping environments, ultimately affecting their product choices and unplanned purchasing. The results also show that more impulsive buyers are more susceptible to these effects. The present article thus complements and constrains prior theorizing on mindset theory, attention, store exploration, and unplanned purchasing, all of which are of practical importance to both retailers and consumers.